HSP27 immunohistochemical expression in colorectal carcinoma: does it have a prognostic role?. Issue 1 (July 2016) - O.K., Rizk; M.A., El-Rashidy
Abstract : Background: Colorectal cancer (CRC) is by far the most common malignancy of the gastrointestinal tract and it is, without question, a 'surgical disease'. The appropriateness of adjuvant therapy and the prediction of outcome for the patient are, to a large extent, based on the pathologic assessment of the local disease and other tissue-based prognostic factors in the resection specimen. Heat-shock proteins are produced in cells constitutively or induced under stress conditions. During carcinogenesis, heat-shock proteins have been reported to show alterations of their expression levels. Overexpression of heat-shock protein 27 kDa (HSP27) has been found in many cancers and may lead to chemotherapy resistance and a poor prognosis. Recent studies have found significant overexpression of HSP27 in CRC and reported a relationship between its everexpression and patient prognosis. It has been implicated in the prognosis of CRC and HSP27-based therapy is of current interest for drug development. Aim: This study aimed to investigate the HSP27 expression and its correlation with the clinicopathological parameters in CRC patients. Materials and methods: Sixty formalin-fixed and paraffin-embedded CRC were obtained from the archive of the Department of Pathology, Faculty of Medicine, Tanta University. Tissues were stained by routine hematoxylin and eosin and examined to confirm diagnosis. Clinical and pathological data were reported. An immnuohistochemical study was carried out using the HSP27 antibody. Results: Low expression of HSP27 was noted in 29 cases studied, most of which were well and moderately differentiated, stages I and II CRC. High expression of HSP27 was noted in 31 cases studied, most of which were moderately and poorly differentiated, stages III and IV. There was a significant correlation between high expression of HSP27 and stages III and IV CRC. Conclusion: HSP27 is a useful prognostic marker in CRC and plays an antiapoptotic role that affects the response to chemotherapy as well as radiotherapy.